The Role of Husband's Social Support and Self-Acceptance in Enhancing Marital Satisfaction among Javanese Women with Involuntary Childlessness: A Cultural and Psychological Perspective - Baiti Nur Isnayanti Wulandari; Arthur Huwae (Universitas PGRI Yogyakarta, 2026)
Javanese women experiencing involuntary childlessness often face strong cultural pressures that can impact their psychological well-being and marital satisfaction. This study aims to examine the relationship between husband’s social support, self-acceptance, and marital satisfaction in Javanese women with involuntary childlessness. Using a quantitative approach and a multiple-correlation design, data were collected from 157 participants via purposive sampling. Instruments included the Social Support Questionnaire (SSQ), Berger's Self-Acceptance Scale, and the ENRICH Marital Satisfaction (EMS) Scale. Analysis using Pearson correlation and multiple regression showed that both husband’s social support and self-acceptance were significantly related to marital satisfaction (F = 96.892; p < 0.001). Social support showed a strong positive correlation (r = 0.712), while self-acceptance had a moderate correlation (r = 0.322), both significant at p < 0.001. These findings highlight the vital role of husband’s support in enhancing self-acceptance and marital satisfaction. The study underscores the importance of relational support within the Javanese cultural context. Keywords: involuntary childlessness, husbands’ social support, marital satisfaction, self-acceptance